PERBANDINGAN HARGA SAHAM DAN VOLUME TRANSAKSI SAHAM SEBELUM DAN SESUDAH PENGUMUMAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) (Studi Kasus Pada Indeks Papan Utama Perusahaan Sektor Perhotelan diBEI): Dibuat Oleh Naila Sa’adah, Yohani, Khoirul Fatah - Y Yohani; Naila Saadah; Khoirul Fatah (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
This study aims to analyze the differences in stock prices and stock transaction volumes in hotel sector companies listed on the main board index before and before announcing the Enforcement of Community Activity Restrictions (PPKM). In this study, there were 3 companies in the hotel sector listed on the main board index which became the research sample using purposive sampling technique. The analytical tool used in this research is the Differential Test. The results of this study indicate that there is no difference in the average share price before and before the announcement of the PPKM. The stock transaction volume variable also shows the same thing, namely there is no difference in the average stock transaction volume before and before the PPKM announcement. However, the results of this study have not specifically described the differences in stock prices and transaction volumes before and before the announcement of the PPKM, so further research is needed. For the issuer concerned, it is hoped that this research can be considered in making decisions that can affect stock prices and transaction volume.